PENGARUH JUS JERUK DAN MINUMAN BERKARBONASI TERHADAP KEKERASAN PERMUKAAN RESIN KOMPOSIT - Rusna Fiki Kafalia; Muh. Dian Firdausy; Arlina Nurhapsari (ODONTO : Dental Journal, 2017)
Background: Orange juice and Carbonat drink contains an acid agent which can affect the surface hardness of composite resin. Changes of surface hardness of composite resin is caused by infiltration of water containing the acid agent that affect the bonding of matrix to filler composite resin. This study purpose to determine the effect of immersed orange juice and carbonat drink on surface hardness of composite resin. Method: This was experimental laboratory study with a pre and post test control group design. The samples of composite resin had 12 mm in diameters and 2 mm in thickness (n=27). Composite resin used is FiltexTM Z350 XT shades A2. Samples were divided into three groups : group A immersed with orange juice, group B immersed with carbonat drink, and group C immersed with aquadest as the negative control. Samples were immersed for 24 hours. The pre and post immertion of composite resin surface hardness were measured with Micro Vickers Hardness Tester. Results: Post immertion Vickers hardness was compared by using one way anova test. The result showed that immersed orange juice and carbonat drink significantly reduced the surface hardness of composite resin (p < 0,05). Concluision: The conclusion Immersed carbonat drink more reduced the surface hardness of composite than orange juice. It is suggested to reduce the duration direct exprossure of consumption carbonat drink.